A Primer on EEG Spectrograms. Issue 3 (March 2022) - Ng, Marcus C.; Jing, Jin; Westover, M. Brandon
Abstract : Summary: As continuous brain monitoring becomes a routine part of clinical care, continuous EEG has allowed better detection and characterization of nonconvulsive seizures, and patterns along the ictal–interictal continuum in critically ill patients. However, this increased workload has led many to turn to quantitative EEG whose central tool is the "spectrogram." Although in relatively wide use, many clinicians lack a detailed understanding of how spectrograms relate to the underlying "raw" EEG signal. This article provides an approachable set of first principles to help clinicians understand how spectrograms encode information about the raw EEG and how to interpret spectrograms to efficiently infer underlying EEG patterns.